MEMIMPIN TIM SECARA EFEKTIF DAN OPTIMAL UNTUK DAPAT MENCAPAI KEBERHASILAN SERTA KESUKSESAN SEPERTI YANG DIINGINKAN OLEH PERUSAHAAN - Wilson, Nicholas; Rowena, Janny; Susilawaty, Lilis; Diayudha, Lanang; Helena, Stevani; Pendi, Marina (Universitas Bunda Mulia, 2021)
ABSTRACT Being able to achieve all of the goals that companies would like to achieve had been the main purpose that all companies in the world want to fulfill, in which, in order to achieve all of these success and goals, companies should be able to lead their teams properly, in which, there are 4 (four) essential factors which companies should fully and thoroughly understand in order to effectively lead all of thsee teams toward achieving the goals that the teams would like to achieve, in which, these four aspects are consisted of: companies’ ability to show and practice leadership, companies’ ability to understand the importance of teamwork and team building, companies ability to develop and execute all of the strategies effectively, and companies’ thorough understanding regarding the methods of tackling or eliminating Silo Mentality. Therefore, this community service project was commenced in order to inform and present the importance of understanding all of these four factors to all of the individuals working within the company in order to enable these individuals (together with their teams) to achieve their goals. This community service activity was conducted in Alfa Land, in which, a total of 37 individuals working in Alfa Land were participating in this community service activity. Due to the COVID-19 pandemic, this community service project was conducted virtually through Zoom Meeting Conference Platform. After commencing this community service project, authors hope that all Individuals and Teams who are participating in this community service activity could further understand the importance of establishing and improving teamwork in order to enable the teams and the company to achieve all of the targets and objectives which the company would like to achieve